2001
DOI: 10.1046/j.1469-1809.2001.6510063.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variability in Russians and Ukrainians: Implication to the origin of the Eastern Slavs

Abstract: In order to investigate the origin of the Eastern Slavs, mitochondrial DNA (mtDNA) sequence variation was examined in Russians and Ukrainians by hypervariable segment I (HVS I) sequencing and restriction analysis of the haplogroup‐specific sites. No significant differences were found for Russians and Ukrainians when compared to other Europeans – in fact, they fall within the range of gene diversity seen throughout Europe and exhibit the unimodal pattern of pairwise sequence differences. Moreover, HVS I sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 27 publications
3
49
0
Order By: Relevance
“…In addition, as the complete sequence data has shown that the 189 325 type is in fact a U5b molecule where a back mutation occurred at 270, 48 haplotype 45 (which is indeed 189 325) is shown to be derived via a back mutation at 270. 45 Haplogroup J, possibly brought to Europe by Neolithic farmers coming from the Near East is found at a frequency of 10% in our sample. It has also been reported elsewhere at 7% in Norway.…”
Section: Uniparental Polymorphisms In Norway G Passarino Et Al 524mentioning
confidence: 79%
“…In addition, as the complete sequence data has shown that the 189 325 type is in fact a U5b molecule where a back mutation occurred at 270, 48 haplotype 45 (which is indeed 189 325) is shown to be derived via a back mutation at 270. 45 Haplogroup J, possibly brought to Europe by Neolithic farmers coming from the Near East is found at a frequency of 10% in our sample. It has also been reported elsewhere at 7% in Norway.…”
Section: Uniparental Polymorphisms In Norway G Passarino Et Al 524mentioning
confidence: 79%
“…In order to compare the present results with other populations, HVRI data from several European, Middle Eastern, Indian, Central Asian, and East Asian populations were taken from the literature: Kazaks, 3 Kyrgyz, 3 Uighurs, 3 , Altaics, 21 Mongolians, 22,23 Daur, 23 Oroqen, 23 Turks, 24 -26 Han Chinese, 17,27 Han Taiwanese, 28 Ainu, 28 Koreans, 23,28,29 Japanese, 28,30 Europeans, 31 Middle Easterns, 31 Caucasus populations, 32,33 Thai, 34 Indians, 35 Russians, 36,37 Ukrainians, 37 and Siberians. 23,38,39 The networks relating HVRI sequences within some of the haplogroups described were constructed by using a reduced-median algorithm 40 as implemented in the Network 3.0 program.…”
Section: Methodsmentioning
confidence: 99%
“…A set of 7245 HVS1 sequences was analysed between sites 16090-16365 (276 base-pairs). In addition to sequences analysed in Helgason et al (2000aHelgason et al ( , 2001, the following are added: 50 Germans (Baasner et al 1998), 106 Sicilians (Cali et al 2001), 118 Spanish (Crespillo et al 2001), 154 Swiss (DimoSimonin et al 2000, 300 Yugoslavian (see Table 2), 20 Finns and 10 Polish (Jorde et al 2000), 50 Russians, (Malyarchuk & Derenko, 2001), 436 Poles and 201 Russians (Malyarchuk et al 2002), 129 Slovakians (E. Metspalu, T. Kivisild, K. Kaldma, M. Reidla & R. Villems, GenBank accession numbers AJ240164-AJ240292), 74 Norwegians (Passarino et al 2002), 241 Portuguese (Pereira et al 2000), 300 Canary Islanders (Rando et al 1999), 83 Italians (Tagliabracci et al 2001) and 186 Cretans (R. Villems, GenBank accession numbers AJ274757-AJ274942). Sequences that did not completely span the regions defined above were omitted from analysis, and population samples analysed in Helgason et al (2000a) with sample sizes below 70 were excluded.…”
Section: Genetic Systems and Population Samplesmentioning
confidence: 99%